1982
DOI: 10.1017/s0021859600054976
|View full text |Cite
|
Sign up to set email alerts
|

Pod and grain yields from intercropping maize andVigna unguiculata(L.) Walp. in Nigeria

Abstract: SUMMARYField experiments were conducted at the International Institute for Tropical Agriculture, Ibadan, Nigeria, during two cropping seasons, with two cultivars of climbing cow peas (Vigna unguiculata (L.) Walp. subspecies sesquipedalis) cv. FARV-13 and TVU-1209. The work investigated their yields when intercropped with maize, which served as live support.The results showed that there were varietal differences in the cow-pea response to method of planting. Under the intercropped systems, highest dry-matter yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
10
1
1
Order By: Relevance
“…In 1998, highest head weight was recorded for sorghum when intercropped with varieties IT90K-277-2 (1791kg/ha) and IT90K-372-1-2 (1750kg/ha) when compared to sole sorghum head weight (1625kg/ha) ( Table 6). This recorded increment in this finding agrees with Wanki et al, 1982 andPal et al, 1993 who had reported yield advantages of legume-cereal intercropping system over sole cropping. However, a significant reduction in head weight was recorded for sorghum when intercropped with varieties IT93K-273-2-1 (1166kg/ha), IT89KD-349 (1250kg/ha) and IT89KD-391 (1375kg/ha).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In 1998, highest head weight was recorded for sorghum when intercropped with varieties IT90K-277-2 (1791kg/ha) and IT90K-372-1-2 (1750kg/ha) when compared to sole sorghum head weight (1625kg/ha) ( Table 6). This recorded increment in this finding agrees with Wanki et al, 1982 andPal et al, 1993 who had reported yield advantages of legume-cereal intercropping system over sole cropping. However, a significant reduction in head weight was recorded for sorghum when intercropped with varieties IT93K-273-2-1 (1166kg/ha), IT89KD-349 (1250kg/ha) and IT89KD-391 (1375kg/ha).…”
Section: Resultssupporting
confidence: 92%
“…The local spreading type is more adapted to intercropping, although the grain yield was low relative to IT86D-716. Wanki et al (1982) reported an increased yield of maize and cowpea when intercropped than when grown as sole crops. Ofori and Stern (1982) reported an increased dry matter production, yield and leaf area index in maize-pigeon pea intercropping system as compared to sole crops.…”
Section: Introductionmentioning
confidence: 99%
“…A later, leafier cowpea cultivar reduced maize yield in association more than an earlier cowpea with lower leaf area index. 90 In India, a pigeonpea cultivar with no basal branching was better for intercropping than traditional branching types. 103 Castor varieties with a dwarf habit and converging branches,' erect petioles, and long spikes are better for intercropping than traditional tall types.…”
Section: Plant Morphologymentioning
confidence: 99%
“…people of the lowland humid tropics has been stated in an earlier paper (Wanki et al 1982). The reasons for practising intercropping and advantages derivable from the practice have been MATERIALS AND METHODS stated in an earlier publication (Wanki, Fawusi & Nangju, 1982).…”
mentioning
confidence: 99%
“…The and pigeon pea (Enyi, 1973). High densities in chemical and physical analysis of the soil and its mixtures have been reported to result in large crop previous history are given by Wanki et al (1982). yield increases: Vanichyangkool (1972) reported A split-plot design with four replications was that highest yield of maize intercropped with soya used.…”
mentioning
confidence: 99%